2015
DOI: 10.1371/journal.pone.0132294
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Valence, Arousal, and Threat Ratings of 160 Chinese Words among Adolescents

Abstract: This study was conducted to provide ratings of valence/pleasantness, arousal/excitement, and threat/potential harm for 160 Chinese words. The emotional valence classification (positive, negative, or neutral) of all of the words corresponded to that of the equivalent English language words. More than 90% of the participants, junior high school students aged between 12 and 17 years, understood the words. The participants were from both mainland China and Hong Kong, thus the words can be applied to adolescents fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Bradley & Lang [2] observed a quadratic relationship between valence and arousal, where highly positive and negative words had higher ratings on arousal. Since then, the same effect has been observed many times in rating studies in different languages, including Finnish [51], Spanish [20,32,64,65], German [34,66], European Portuguese [22], and Chinese [36]. A step-wise regression analysis with a linear and a quadratic term was performed, with valence and its square as the independent variables and arousal as the dependent variable.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Bradley & Lang [2] observed a quadratic relationship between valence and arousal, where highly positive and negative words had higher ratings on arousal. Since then, the same effect has been observed many times in rating studies in different languages, including Finnish [51], Spanish [20,32,64,65], German [34,66], European Portuguese [22], and Chinese [36]. A step-wise regression analysis with a linear and a quadratic term was performed, with valence and its square as the independent variables and arousal as the dependent variable.…”
Section: Resultsmentioning
confidence: 66%
“…There are only a few studies on psycholinguistic properties of two-character words, and no study has considered both affective and lexico-semantic variables, both objective and subjective ones, within the same study. While Ho et al [36] and Wang et al [37] provided affective ratings for 160 and 1500 two-character words respectively, lexico-semantic variables were not collected in these studies. More recently, Yao et al [38] collected both affective and lexico-semantic ratings for 1100 words, but did not provide objective word frequency information for the words.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that interpretation bias has an effect on memory performance among depressed individuals (Everaert, Tierens, Uzieblo, & Koster, ). Furthermore, because the valence rating of words may vary across populations (Ho et al., ), it is possible that some of our participants might have appraised the neutral words used in our experiments as negative‐valence words, leading to our finding that the positive relationship between depressive symptoms and negative‐valence words also applied to neutral words. A previous study used complex pictures in a DF experiment (Hauswald & Kissler, ), and positive and negative pictures are commonly used (e.g., in the visual dot‐probe experimental paradigm) to investigate attentional bias (Chan, Ho, Tedeschi, & Leung, ; MacLeod & Mathews, ; MacLeod, Mathews, & Tata, ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to measuring the processing of emotionality in words for bilinguals, this study will also provide information about how the characteristics of the language may play a role in emotionality. Chinese is very distinctive and the difference between Chinese and English is much greater than the differences between English and languages such as Spanish, Dutch, and French [45] [5].…”
Section: E Aims and Intentions Of The Current Experimentsmentioning
confidence: 99%
“…This also indicates that words carry both a semantic meaning and an emotional meaning via amygdala mediated learning. Based on this, early theoretical frameworks have posited that language and emotion are highly interlinked [3][4] [5]. For example, research has shown that language can influence the intensity of emotions (including anger, disgust, fear, and sadness) being experienced and perceived [6].…”
Section: Introductionmentioning
confidence: 99%